Penerapan Activity Based Costing Untuk Menentukan Harga Pokok Produksi Dalam Rangka Meningkatkan Keunggulan Kompetitif - Winda Aulia Fadhilah; Etti Ernita Sembiring; Lili Indrawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
PT Multi Instrumentasi needs to increase its competitive advantage in order to face business competition. This study aims to determine the comparison between the cost of production using the ABC method and the traditional method, and to find out the benefits of implementing ABC in increasing competitive advantage at PT Multi Instrumentasi. This study uses a quantitative descriptive method. The types of data used are quantitative data and qualitative data. The data sources are primary data and secondary data. Methods of data collection by interview, observation and documentation. The data analysis technique used is the calculation of the cost of production using the traditional method and the ABC method, as well as calculating the selling price to be compared with the selling price of competitors. The results show that the application of ABC can help companies increase their competitive advantage by reducing cost distortions so that the calculation of the cost of production becomes accurate, the selling price is set to be precise and lower than competitors. ABC also provides activity information that can help companies to streamline costs and increase customer value.